Local Application of High-Frequency Laser Ultrasound in the Complex Treatment of Patients with Puturous Inflammation of the Face - Jaw Area - Z., Muhammedov Z.; Rakhimov Z. K. (Research Journal of Trauma and Disability Studies, 2024)
It's sharp purulent inflammation diseases effect wide circular combined antibacterial drug - amoxicillin and clavulanate acid in cereal complex of treatment indicators given . The effect wide circular combined antibacterial drug - amoxicillin and clavulanate acid many p numerous aerobic and anaerobic to microorganisms effect that he did because of , him success with in the area of the face and jaw sharp purulent inflammation diseases in treatment apply can.